20.7k views
1 vote
Does someone mind helping me with this problem? Thank you!

Does someone mind helping me with this problem? Thank you!-example-1

2 Answers

4 votes


(10-(3 \cdot 2^2 - 23))/((1 + 10^2)-2^2 \cdot 5^2) =


10-\left(3\cdot \:2^2-23\right) =10-\left(-11\right) =21


\left(1+10^2\right)-2^2\cdot \:5^2 = 101-2^2\cdot \:5^2 = 101-4\cdot \:5^2 =101-4\cdot \:25 =101-100 = 1


=(21)/(1)


(a)/(1)= a


=21

I hope I helped you!

User Krishnakant Kadam
by
5.1k points
11 votes

Let's simplify ~


\qquad \sf  \dashrightarrow \: \frac{10 - (3 * 2 {}^(2) - 23) }{(1 + 10 {}^(2)) - {2}^(2) * {5}^(2) }


\qquad \sf  \dashrightarrow \: \frac{10 - (3 * 4{}^{} - 23) }{(1 + 10 0{}^{}) - {4}^{} * {25}^{} }


\qquad \sf  \dashrightarrow \: \frac{10 - (12- 23) }{(10 1{}^{}) - {100}^{} }


\qquad \sf  \dashrightarrow \: (10 - ( - 11) )/(1)


\qquad \sf  \dashrightarrow \: 10 + 11


\qquad \sf  \dashrightarrow \: 21

User Prabhat Maurya
by
6.6k points